Developments in the Synthesis of 1,2-Dihydropyridines - Silva, Eduarda M. P.; Varandas, Pedro A. M. M.; Silva, Artur M. S. (Synthesis, 2013)
This review provides a comprehensive compilation of available literature concerning the synthesis of 1,2-dihydropyridines. The most important recent developments and concepts related to this topic are emphasised.1 Introduction2 Synthesis of 1,2-Dihydropyridines2.1 Condensation Reactions2.2 Reduction of Pyridines and Pyridinium Salts2.3 Nucleophilic Addition to Pyridines and Pyridinium Salts2.4 Pericyclic Reactions2.5 Other Methods3 Conclusions
Keywords: dihydropyridines; NADH; isoquinuclidines; pericyclic reactions; heterocyclic compounds